Pengaruh Kecepatan Jaringan Internet terhadap AI Image Generator - Anggit Rangga Putra; Mahmudin Mahmudin (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
This research aims to analyze the performance comparison of several AI Image Generator platforms in generating images based on text prompts, considering the influence of internet speed on rendering time. The platforms tested include Blackbox AI, Craiyon AI, Dreamina AI, and Freepik AI. Testing was conducted using two types of internet providers, namely XL and Indihome, to evaluate differences in rendering time and the accuracy of the generated images. The results indicate that internet speed significantly affects rendering time, with Freepik AI showing the greatest impact. Additionally, the accuracy of the generated images varies depending on the platform's ability to translate text prompts into images. These findings provide insights into the factors influencing the performance of AI Image Generators, particularly in the context of internet speed and output accuracy.